Balancing Environmental and Economic Considerations in Horizontal Alignment Optimization of a Ring Road near Anzali International Wetland - Saeid Aftabi Hossein; Kamran Rahimov (Environmental Energy and Economic Research)
Roads are the primary transportation infrastructure of every country and play a crucial role in achieving sustainable economic development. Neglecting environmental considerations in civil engineering projects, especially in the design and construction of roads, can cause extensive damage to human societies and ecosystems. One of the most critical issues in road design is selecting an optimal alignment that minimizes changes to land use, preserves wetlands, forests, and agricultural land, and provides a platform for sustainable development. This decision has a significant impact on the execution, operation, and maintenance costs of the route, as well as its surrounding geography. This research examines the optimal horizontal alignment between two desired starting and ending points, taking into account environmental factors, construction cost parameters, and safety indices in the Anzali ringroad highway area. The route design data was collected and the important variables affecting the route design were determined. Then, the optimal balance was evaluated using the genetic algorithm method. After analyzing the generated data, we propose the optimal horizontal alignment as the final recommended option, with four horizontal arcs and a length of 14.991 kilometers. This alignment is compatible with the environment and has significantly lower greenhouse gas emissions, resulting in a cost savings of 3.7 million dollars compared to the initial alignment. It is a desirable and shorter horizontal alignment between two points in one of the important areas of the Ramsar International Convention (Anzali).